2019
DOI: 10.1016/j.radonc.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance doses for late adverse events after hypofractionated radiotherapy for prostate cancer on trial NRG Oncology/RTOG 0415

Abstract: Purpose/Objective: Hypofractionated radiotherapy (HRT) regimens for prostate cancer are emerging, but tolerance doses for late adverse events are scarce. The purpose of this study is to define dose-volume predictors for late gastrointestinal and genitourinary (GI and GU) toxicities after HRT in the multi-center NRG/RTOG 0415 low-risk prostate cancer trial (N=521). Material/methods: Treatment in the studied HRT arm was delivered as 70Gy at 2.5Gy/fraction with 3D-CRT/IMRT (N=108/413). At a median follow-up of 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Our attitude was to establish a better way to treat all patients who can benefit from radiotherapy; not to delay the onset of any patient whose deferral may worsen the prognosis of their disease; try to help the patient attend treatment as few times as possible and not increasing toxicity and maintaining the possibility of the best result. The hypofractionated treatments we indicated during the time of COVID-19 are supported mainly by international guidelines and phase III clinical trials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Our attitude was to establish a better way to treat all patients who can benefit from radiotherapy; not to delay the onset of any patient whose deferral may worsen the prognosis of their disease; try to help the patient attend treatment as few times as possible and not increasing toxicity and maintaining the possibility of the best result. The hypofractionated treatments we indicated during the time of COVID-19 are supported mainly by international guidelines and phase III clinical trials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…It should be also noted that the recent ASTRO, ASCO and AUA Evidence-based guideline on hypofractionated RT does not recommend non modulated 3DCRT techniques when delivering MHRT [27]. Therefore, unlike other Authors [9,17], we focused on patients treated with IMRT/VMAT only.…”
Section: Discussionmentioning
confidence: 99%
“…Dose-volume objectives are placed at planning on the rectum (or the rectal wall-RW) in order to control for (and possibly) limit its dosage. However, there are scarce data looking at the relationship between individual dose/volume metrics and late rectal toxicity in the setting of MHRT [9,[16][17][18] particularly regarding the 20fraction schedule that is widely supported by the available trials https://doi.org/10.1016/j.ctro.2020.01.006 2405-6308/Ó 2020 The Authors. Published by Elsevier B.V. on behalf of European Society for Radiotherapy and Oncology.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, although many candidate structures, such as the whole bladder, bladder trigone and urethra, have been proposed for genitourinary toxicity [30e32], none has consistently been shown to predict toxicity. In the dosimetric analysis of RTOG 0415 [29], no correlation between bladder dose and physician-reported toxicity could be found. For erectile dysfunction, accumulating evidence suggests that dose to the penile bulb is correlated with long-term erectile dysfunction [33e35].…”
Section: Toxicity Outcomes Of Moderate Hypofractionationmentioning
confidence: 91%
“…Gulliford et al [26] confirmed a relationship between the number of constraints 'missed' in the RT01 trial with clinician-reported toxicity. Thor et al [29] retrospectively analysed the randomised RTOG 0415 trial and found that restricting the minimum dose to the hottest 5% of the rectum to 62 Gy EQD2 (a/b 3 Gy) would reduce grade 2 þ RTOG toxicity from 20% (assuming the D5% was >65 Gy) to 10% [29]. Therefore, standard fractionation radiotherapy can now be optimised to minimise the risk of rectal sideeffects and, as shown in Ferreira et al [27] recently, if these constraints are respected, the chance of toxicity with conventional hypofractionation is low.…”
Section: Toxicity Outcomes Of Moderate Hypofractionationmentioning
confidence: 99%